2009
DOI: 10.22358/jafs/66361/2009
|View full text |Cite
|
Sign up to set email alerts
|

Application of nutrigenomics tools in animal feeding and nutritional research

Abstract: The development of nutrigenomic studies has brought about a number of new research tools (transcriptomics, proteomics and metabolomics), which are important in animal nutrition and food research. This review presents an overview on the application of nutrigenomics tools in this scientifi c area. The use of microarray technologies -the main tools of transcriptomics, has allowed new information concerning the physiological effect of different dietary proteins, of omega-3 polyunsaturated fatty acids and dietary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…Animal nutrition research has demonstrated that gene expression can be modified by dietary components (Zduńczyk & Pareek ), but the molecular mechanisms involved are still poorly understood and little is known about the role of plant feed ingredients in the expression of genes involved in modulation of the fish immune system (Montero et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal nutrition research has demonstrated that gene expression can be modified by dietary components (Zduńczyk & Pareek ), but the molecular mechanisms involved are still poorly understood and little is known about the role of plant feed ingredients in the expression of genes involved in modulation of the fish immune system (Montero et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrigenomic tools (i.e. transcriptomics) are increasingly used to investigate molecular events taking place in a genome receiving nutritional signals and responding to them through characteristic metabolic processes in the organism (12) . Nutrigenomics studies in farmed fish have addressed the replacement of different percentages of FM and/or FO with plant ingredients in diets (13)(14)(15) , and the effects of such replacement are well characterised in the hepatic transcriptome of salmonids (10,(16)(17)(18) and marine species such as sea bass (14) .…”
mentioning
confidence: 99%
“…156 A aplicação dessas novas áreas pode ser comprovada pela extensa compilação de trabalhos encontrados na literatura. [157][158][159][160][161][162] A nutrimetabolômica, que se refere à aplicação da metabolômica na área de nutrição, permite a caracterização de fenótipos individuais, por meio da medida de centenas ou milhares de metabólitos, após a exposição a uma dieta específica, por exemplo. De um modo geral, a nutrimetabolômica está focada na descoberta de biomarcadores por meio da avaliação do efeito de uma dieta, 163 estudos de intervenção de dieta em uma rota metabólica, 164,165 e estudo da relação dieta-doença 157 ou, mais recentemente, na busca de uma dieta personalizada.…”
Section: Foodomics E Nutriçãounclassified